1982
DOI: 10.1002/j.1552-4604.1982.tb05709.x
|View full text |Cite
|
Sign up to set email alerts
|

Saline Catharsis: Effect on Aspirin Bioavailability in Combination with Activated Charcoal

Abstract: The effect of a saline cathartic combined with activated charcoal or activated charcoal alone on aspirin bioavailability was characterized in six healthy volunteers. Using a random, Latin-square design, subjects were given 975 mg aspirin followed by either water alone, 15 Gm activated charcoal (AC), or 15 Gm activated charcoal plus 20 Gm sodium sulfate (AC + SS) separated by one week. Both AC (44.16 +/- 16.85 microgram/ml) and AC + SS (58.61 +/- 10.63 microgram/ml) decreased (P less than 0.001) the maximal pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In experimental animals there is some but not unambiguous evidence that purgatives would increase the antidotal efficacy of oral activated charcoal (Laass, 1980;Chin et al, 1981;Picchioni et al, 1982;Van de Graaff et al, 1982;Gaudreault et al, 1985). Human studies have failed to show any substantial beneficial effects of purgatives in combination with charcoal (Mayersohn et al , 1977;Easom et al , 1982;Sketris et al , 1982; Galinsky & Levy, 1984).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In experimental animals there is some but not unambiguous evidence that purgatives would increase the antidotal efficacy of oral activated charcoal (Laass, 1980;Chin et al, 1981;Picchioni et al, 1982;Van de Graaff et al, 1982;Gaudreault et al, 1985). Human studies have failed to show any substantial beneficial effects of purgatives in combination with charcoal (Mayersohn et al , 1977;Easom et al , 1982;Sketris et al , 1982; Galinsky & Levy, 1984).…”
Section: Discussionmentioning
confidence: 92%
“…In experimental animals purgatives have either improved (Laass, 1980;Chin et al , 1981;Picchioni et al , 1982;Gaudreault et al , 1985) or diminished (Van de Graaff et al, 1982) the antidotal efficacy of charcoal. Studies in man have failed to demonstrate any substantial benefit from the combined use of purgatives and charcoal (Mayersohn et al 1977;Easom et al , 1982;Sketris et al, 1982;Galinsky & Levy, 1984). However, there seems to be no information concerning the effects of other than saline and osmotic purgatives on the antidotal efficacy of charcoal in man.…”
Section: Introductionmentioning
confidence: 91%
“…There is no evidence that single-dose charcoal has a constipating effect, with the mean time to first stool being 23.5h (Krenzelok et al 1985). Minimising the effects of desorption by decreasing gastrointestinal transit time is an attractive hypothesis, but 5 human studies did not show decreased drug absorption when carthartics were added to charcoal (Easom et al 1982;Mayersohn et al 1977;McNamara et al 1988;Neuvonen & Olkkola 1986;Sketris et al 1982). A modest treatment effect of a 14.2% decrease in salicylate absorption when sorbitol was added to charcoal was demonstrated by Keller et al (1990), which is of questionable clinical significance.…”
Section: Concomitant Cathartic Therapymentioning
confidence: 93%
“…Activated charcoal, single-dose There were 13 clinical trials (level 1b) that examined the effect of activated charcoal on aspirin absorption (193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205). None of these studies was performed as out-of-hospital care.…”
Section: Treatment Measuresmentioning
confidence: 99%
“…One study showed it to be more efficacious than ipecac syrup (195), but another study found that both treatments were equally efficacious (196). The addition of magnesium citrate to activated charcoal had little effect on the efficacy of charcoal in two studies (198,205). The addition of sorbitol improved the efficacy of activated charcoal in one study (200), but reduced it in another (202).…”
Section: Treatment Measuresmentioning
confidence: 99%